Pengaruh globalisasi terhadap pendidikan Islam termasuk tantangan modernisasi dan perkembangan teknologi - Kusmira, Lidia; Gultom, Yusrina; Nasution, Abdusima (Indonesian Institute for Counseling, Education and Theraphy, 2024)
Globalization has had a significant impact on various aspects of life, including Islamic education. The process of globalization, characterized by increasing interconnectedness between countries and rapid advancements in information technology, influences the education system, curriculum, teaching methods, and the values being taught. On one hand, globalization offers opportunities for Islamic education to evolve and adapt to the demands of the times, but on the other hand, it also presents challenges related to modernization and the integration of technology, which may not always align with the core principles of Islamic teachings. This study employs a literature review method to explore the impact of globalization on Islamic education, with a focus on the challenges arising from modernization and technological development. Data are gathered from various relevant sources, such as books, journal articles, and research reports discussing related issues. The objective of this research is to understand the effects of globalization on Islamic education, as well as to identify the challenges and opportunities that emerge as a result of these changes. This study also aims to provide insights into strategies that Islamic educational institutions can adopt to address these challenges while maintaining the traditional values that underpin Islamic education. In conclusion, globalization has a complex impact on Islamic education, both positively and negatively. While there is great potential to improve education quality through increased access to information and technology, challenges such as value shifts and threats to the integrity of Islamic teachings must be addressed with caution. Therefore, Islamic education must be able to adjust to the evolving times, while preserving the essence of Islamic teachings to remain relevant and capable of producing competent and morally upright generations.